Nuove forme di ‘angoscia territoriale’: il caso Viggiano. Strategie culturali di un territorio in crisi - Marialuisa Matera (Archivio Antropologico Mediterraneo)
This article examines the individual and collective perception of the health risks associated with the extraction of hydrocarbons in Basilicata. Viggiano (Val d’Agri, province of Potenza), green-oil heart into the park of the Appennino Lucano Val d’Agri Lagonegrese, is a globalized hyper-place. Since the beginning of the last century, Viggiano has shifted from the typical anonymity of a small reality of Southern Italy to the heart of national political events and global economic choices that have elected it the "oil capital of Italy". Starting from the results of an ethnographic research carried out during 2016, the article will focus on the analysis of the existential bond between the population and the territory. In particular, to think about the current critical points of this connection, it will be explained the concepts of health and illness according to the meaning they assume in the valley.